Sistem Informasi Pemesanan Tiket Tempat Wisata Berbasis Website - Marini Styawati; Riyan Abdul Aziz; Hadis Turmudi (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2023)
This study is titled Ticket Reservation Information System For a Website-Based Tourist Destination a Case Study of Bale Rantjah Park. The aim of this research is to design and develop a ticket reservation information system to facilitate visitors in booking tickets, enhance ticket management for Bale Rantjah Park, and modernize the conventional ticket reservation system. The research employs a qualitative descriptive approach, utilizing data collection methods such as observation, interviews, and literature review. The outcome of this study is a web-based ticket reservation information system that enables visitors to easily make online ticket bookings. Users can access information about the tourist destination, make reservations by selecting the amount of tickets and visit dates, and proceed with online payments. Administrators can manage visitor data and transactions, as well as generate revenue reports. In conclusion, this web-based ticket reservation information system offers advantages and convenience for both visitors and the management of Bale Rantjah Park. The implementation of this system is expected to streamline ticket reservations and data management, provide an improved experience for visitors, and support the growth of the tourism business.